CLINICAL ASPECTS AND PICTURE OF EPILEPSY - Yakutkhon Madjidova; Shokirjon Mamatkurbonov (International Scientific and Current Research Conferences, 2021)
Epilepsy is a chronic polyethiological disease of the brain, characterized by repeated (2 or more) spontaneous (unprovoked) seizures, which are caused by excessive hypersynchronous discharges of neurons in the cerebral cortex, and are manifested by sudden transient neurological dysfunction (disorders of motor, sensory, autonomic, mental or mental functions ), as well as, almost always, impaired consciousness. More precisely, epilepsy is a whole group of diseases, or forms of epilepsy (syndromes) that have their own specific characteristics.